The Words of nature in the poetry of Muhammad saeed Al-Haboubi - Yaqeen kareem kadeem; Dr. Muhammed Mizel Al-Khalat (Journal of College of Education, 2024)
The research deals with the subject of nature for the poet Muhammad Saeed Al-Haboubi and the extent of the influence of nature on the poet and his influence on it, as it was a primary source of his image and a source of his poetry. From a poet whose poems are devoid of nature, nature has a great importance in the imagination of poets, as they find through it the expression of what is in their minds and through which many images and meanings emerge.